NEDD4 degrades TUSC2 to promote glioblastoma progression. (10th April 2022) - Rimkus, Tadas K.; Arrigo, Austin B.; Zhu, Dongqin; Carpenter, Richard L.; Sirkisoon, Sherona; Doheny, Daniel; Regua, Angelina T.; Wong, Grace L.; Manore, Sara; Wagner, Calvin; Lin, Hui-Kuan; Jin, Guangxu; et al.
Abstract: Whether tu mor s uppressor c andidate 2 (TUSC2) plays an important role in glioblastoma (GBM) progression is largely unknown. Whether TUSC2 undergoes polyubiquitination is unknown. Herein, we report that TUSC2 protein expression is reduced/lost in GBM compared to normal brain due to protein destabilization; TUSC2 mRNA is equally expressed in both tissues. NEDD4 E3 ubiquitin ligase polyubiquitinates TUSC2 at residue K71, and the TUSC2-K71R mutant is resistant to NEDD4-mediated proteasomal degradation. Analysis of GBM specimens showed NEDD4 protein is highly expressed in GBM and the level is inversely correlated with TUSC2 protein levels. Furthermore, TUSC2 restoration induces apoptosis and inhibits patient-derived glioma stem cells (PD-GSCs) in vitro and in vivo . Conversely, TUSC2-knockout promotes PD-GSCs in vitro and in vivo . RNA-Seq analysis and subsequent validations showed GBM cells with TUSC2-knockout expressed increased Bcl-xL and were more resistant to apoptosis induced by a Bcl-xL-specific BH3 mimetic. A TUSC2-knockout gene signature created from the RNA-seq data predicts poor patient survival. Together, these findings establish that NEDD4-mediated polyubiquitination is a novel mechanism for TUSC2 degradation in GBM and that TUSC2 loss promotes GBM progression in part through Bcl-xL upregulation. Highlights: TUSC2 protein is destabilized in GBM but not in astrocytes. NEDD4 E3 ligase polyubiquitinates TUSC2 protein at Lys71, leading to TUSC2 degradation in a proteasome-dependent manner. TUSC2 restoration induces apoptosis and inhibits glioma stem-like cells in vitro and suppresses glioblastoma growth in vivo. TUSC2-knockout inhibits apoptosis and promotes glioma stem-like cells in vitro and enhances glioblastoma growth in vivo. TUSC2-knockout significantly altered GBM transcriptome; TUSC2-knockout Gene Signature predicts poor GBM patient survival.